Evaluating the Quality of Online Courses: Challenges and Strategies for Success - Stephanie Boss Dr.; Dana Hilbert Dr.; Mary Dzindolet Dr.; Jennifer Dennis Dr. (Academic Chairpersons Conference Proceedings, 2019)
The department chairs of Education, Sports & Exercise Science, and Psychology and their dean, share their process for evaluating the quality of online courses with faculty in existing and newly developed courses. Training, internal and external reviews, and implementation strategies will be discussed in this session.
Keywords: Online Courses; Quality Assurance; Quality Matters; Course Design; Distance Learning